Are Genetics Involved in the Development of Multisystem Inflammatory Syndromes in Children? - Sevcan Ipek; Ufuk Utku Güllü (Trends in Pediatrics)
The relationship between Multisystem Inflammatory Syndrome in Children (MIS-C) and genetic predisposition is not well established. The aim of this article emphasize the presence of genetic predisposition in MIS-C by presenting two sibling cases from two separate families with a diagnosis of MIS-C. The patients applied with complaints of fever, abdominal pain, diarrhea and maculopapular rash. While the coronavirus disease-2019 (COVID-19) polymerase chain reaction test was negative in all cases, three had both IgM and IgG positivity, and the other case had only IgG positivity. Patients who did not define any other infection were diagnosed with MIS-C according to the Centers for Disease Control and Prevention criteria. The patients were discharged with full recovery. The fact that siblings share the same genetic background and the same environmental factors suggests that MIS-C syndrome occur in individuals with a genetic predisposition. Further genetic studies with a large MIS-C series are needed to determine which genotypic trait may cause the development of MIS-C in COVID-19 infection.